PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI DENGAN FOTOGRAFI - Nur Shendy Lutfiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
ABSTRACT Seeing the rapid development of technology and information, nowadays Instagram is the right choice for business people. Instagram itself also has features that are very useful for business people to promote their business with all the conveniences and features available in it. In the study